PENGARUH BAURAN PEMASARAN TERHADAP KEPUTUSAN PEMBELIAN PRODUK SCARLETT WHITENING DI CIKARANG - Ibnu Cahyo Ramadhan; Muhammad Edy Supriyadi; Tia chisca Anggraeni; Lista Kuspriatni; Agus Sujarwanto (LP2M Universitas Bina Bangsa, 2024)
The purpose of this study was to analyze the influence of marketing mix on the purchase decision of scarlett whitening products. The analysis method in this study using quantitative primary data, the test stages carried out are: validity, reliability, normality, multiple linear regression analysis, F test, t test and coefficient of determination. The data used in this study used a questionnaire instrument with a Likert scale, and valid data that was collected as many as 100 respondents. The sampling method in this study is non-probability sampling with purposive sampling techniques. The testing tool used is SPSS 25. The results showed that variables in the marketing mix, namely products, places, and promotions, had a partial effect on purchasing decisions, while price variables did not partially affect purchasing decisions